2011
DOI: 10.1021/pr200030v
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Protein Profiling of Adipose-Derived Human Stem Cells under Hyperosmotic Treatment

Abstract: Our previous work suggested that treatment of cells with hyperosmotic media during 2D passaging primes cells for cartilage tissue engineering applications. Here, we used label-free proteomic profiling to evaluate the effects of control and hyperosmotic treatment environments on the phenotype of multipotent adipose-derived stem cells (ASCs) cultivated with a chondrogenic growth factor cocktail. Spectra were recorded in a data-independent fashion at alternate low (precursor) and high (product) fragmentation volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Analysis of peptides was performed at the Quantitative Proteomics Center at Columbia University using an ultrahigh-pressure liquid chromatograph and a quadrupole-time-of-flight mass spectrometer using methods described previously (Oswald et al, 2011). This system uses a shotgun proteomics method called MS E in which mass spectra are recorded at alternate low (precursor) and high (product) fragmentation voltages (Silva et al, 2006), resulting in a more complete representation of the intensity of a peptide in a chromatographic peak.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of peptides was performed at the Quantitative Proteomics Center at Columbia University using an ultrahigh-pressure liquid chromatograph and a quadrupole-time-of-flight mass spectrometer using methods described previously (Oswald et al, 2011). This system uses a shotgun proteomics method called MS E in which mass spectra are recorded at alternate low (precursor) and high (product) fragmentation voltages (Silva et al, 2006), resulting in a more complete representation of the intensity of a peptide in a chromatographic peak.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, 1,016, 790, and 1,104 proteins in bMSCs, ASCs, and fibroblasts were identified, respectively, which suggest that the extraction and labelfree proteomics analysis in our study are more sensitive. Label-free analysis of bone marrow-sourced stem cells has also been utilized previously to study the function of tissues (Han, Hong, & Park, 2019) and in the characterization of cellular responses to chondrogenic treatment regimens (Oswald, Brown, Bulinski, & Hung, 2011). In particular, our PCA results illustrate a significant separation of 2D…”
Section: Proteomics Analysis Reveals the Role Of Isr In Msc Homeostmentioning
confidence: 60%
“…Source: Suppl. Table 1 of Oswald et al (2011) . ΩfAⒶ ΩgAⒶ Mannitol-balanced 5.5 (control), 25 or 100 mM d -glucose media.…”
Section: Methodsmentioning
confidence: 99%